Management of resistant Conyza spp. During soybean pre-sowing - Cesco, V. J.S. [UNESP]; Nardi, R.; Krenchinski, F. H. [UNESP]; Albrecht, A. J.P.; Rodrigues, D. M. [UNESP]; Albrecht, L. P. (FapUNIFESP (SciELO), 2019)
Horseweed (Conyza spp.) is a weed with a considerable presence and frequency throughout Brazilian crops, as well as presenting difficult chemical control. The objective of this study was to evaluate the efficiency of herbicide management, through single and sequential applications, in controlling Conyza spp., at two development stages with 4 to 6 leaves (3 to 5 cm) and 20 leaves (15-20 cm). The analyzed variables were: control percentage (7, 14, 21, and 28 days after application), dry matter content (28 days after application) and regrowth percentage (21 days after application). Data were submitted to analysis of variance at 5% probability and when there was a difference, the means were submitted to the Scott-Knott test. For Conyza spp. plants with a height between 3 and 5 cm and 4 to 6 leaves, the best treatments were T4, T8, T9, T10, T11, T12, T13, and T14, presenting a control percentage above 90%, 7 days after application. For Conyzaspp. plants with a plant development of 15 cm in height and 15 to 20 leaves, the highest control percentages and lowest regrowth percentages were with treatments T9, T13, and T14.
Manejo de conyza spp. Resistente em pré-semeadura da soja
Keywords: 2.4-D; Early management; Regrowth; Saflufenacil; Sequential